Elementary school pupils’ concepts about digestive system - Petr; Kubiatko, Milan; Dominika (Scientia in educatione, 2023)
The concepts about any kind of phenomena are developing from the early age of child with the influence of external factors. The main aim of the diploma thesis was to find out primary school pupils’ concepts about digestive system, and to determine the effect of different factors. The most important factor is the transition of pupils from the primary to secondary level of elementary schools. The sample size was created by elementary school pupils (n = 193). The research tool was divided into three parts, the first one was focused demographical variables, the second one was focused on the perception of perceived vulnerability. The last part of research tool was focused on the concepts of pupils about digestive system through methods of children’s drawings. The methods of descriptive and inductive statistics were used for the data analysis. The 5th grade pupils achieved the highest score, the pupils of 1st and 9th grades achieved the lowest one. The pancreas was the most missing organ in the drawings. The implications for pedagogical practice are suggested in the conclusion.